Effects of epigenetic modification and ionic liquid on DNA charge transport : applications in biology and material - Xuan, Shuguang (2016)
The well-aligned base pairs along the DNA central axis serve as a convenient pathway for charge migration. The phenomena termed as DNA charge transport (CT) has stirred up great interests about the underlining mechanism, biological roles and potential applications in development of DNA based electronic devices. Mechanistic investigations have revealed that various factors might affect the process of DNA CT, including inherent factors, such as the base pairs composing the "bridge" for charge migration, secondary structures and sequences of duplex DNA; and external factors, such as protein binding, external magnetic fields and solvents. The biological significance of DNA CT has been found to be associated with several redox processes in cell, such as funnelling oxidative stress, and signalling between proteins. On the other hand, applications of DNA CT in molecular electronics have been extensively studied to develop multi-functional DNA electronic devices. Despite the great achievements of previous studies with regards to DNA CT, further research is demanded to advance DNA CT to a higher step in its application biology and material. This thesis explored via two approaches: modulating DNA CT by epigenetic modification on base pair stacks and facilitating DNA CT by using hydrated ionic liquid as solvents. The attempts here provide critical progress in understanding biological functions of DNA CT and developing protocols to make DNA a better conductive biomaterial.